TEACHING ENGLISH LANGUAGE VIA GAMES - Khusanov Elyor Egamberdi oʻgli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract.This paper suggest that the importance of teaching English language via games and the role of games in teaching learners.In this article analyse that games can significantly enhance the learning experience by engaging students in a interactive environment. Through a detailed analysis, the paper demonstrates how games facilitate the acquisition of vocabulary and the development of speaking skills among learners.